The geometry, kinematics, and timing of deformation along the southern segment of the Paposo fault zone, Atacama fault system, northern Chile. (January 2020) - Ruthven, Rachel; Singleton, John; Seymour, Nikki; Gomila, Rodrigo; Arancibia, Gloria; Stockli, Daniel F.; Ridley, John; Magloughlin, Jerry
Abstract: The Paposo fault zone is a major brittle-ductile strand of the Atacama fault system (AFS), which records sinistral shear associated with Cretaceous oblique subduction beneath northern Chile. New detailed geologic mapping, macro- and microstructural data, and zircon geo/thermochronology reveal insight into the structural evolution of the southern portion of the Paposo fault. The core of the Paposo fault is defined by a ~50 m-thick zone of illite-rich gouge that dips steeply ESE and juxtaposes fractured but unfoliated Early Jurassic tonalite west of the fault against mylonitic Late Jurassic to Early Cretaceous granitoids east of the fault. The mylonite zone east of the fault is ~0.7–1 km thick and includes a ~100–500 m-thick band of hydrothermally-altered ultramylonite derived from Latest Jurassic (146.5 ± 1.5 Ma) to Early Cretaceous (138.5 ± 1.6 Ma) granodiorite. West of this ultramylonite zone, a ~150–350 m-thick zone of younger tonalite (136.0 ± 1.8 Ma) parallels the Paposo fault and grades from protomylonite to mylonite <10 m from the gouge zone on its western margin. Mylonitic foliations dip steeply to moderately SE with lineations that typically plunge ~10–30° SW. Most SE-dipping mylonitic fabrics record oblique sinistral-reverse shear that is consistent with the overall pattern of small-scale brittle faults and S-C-C' fabrics in the Paposo fault gouge zone. However, in several parts of the hydrothermally-altered mylonite zone, symmetric microstructures and S > L tectonite fabrics most likely record a significant component of zone-normal flattening. The upper age limit of deformation is constrained to be younger than the Late Jurassic/Early Cretaceous granodiorite. Hydrothermal alteration and development of high-strain zones in the Late Jurassic/Early Cretaceous granodiorite are locally associated with mafic dikes that do not cut the younger protomylonitic tonalite, indicating that most of the hydrothermal alteration and mylonitic strain occurred between ~139 Ma and 136 Ma. The Paposo fault gouge zone formed between 150 °C and 200 °C based on clay mineralogy and the illite Kübler index. The timing of gouge formation most likely overlaps with cooling below ~180–190 °C recorded by a zircon (U-Th)/He date of 116.6 ± 6.2 Ma from the Late Jurassic/Early Cretaceous granodiorite. Together these data constrain brittle and ductile deformation to the Early Cretaceous, similar to the age of deformation along other segments of the AFS and coeval with co-spatial arc magmatism. Regionally, the Paposo segment of the AFS is arcuate, trending NNW-SSE in the northern end and NNE-SSW in the southern end. Previous studies of fault strands along the northern portion of the Paposo segment document sinistral transtension, whereas oblique sinistral-reverse shear and local coaxial flattening record sinistral transpression along the southern portion of the Paposo fault. We propose that transtension and transpression along the AFS are controlled by the arcuate geometry, and both are compatible with sinistral simple shear along the N-S-trending magmatic arc. Highlights: The NNE-striking Paposo fault zone records brittle-ductile sinistral transpression. High-strain mylonites formed from ~139 to 136 Ma; minor strain continued after ~136 Ma. Mylonitization was coeval with arc plutonism along the shear zone. Foliated clay gouge in the Paposo fault core formed at 150–200 °C around 117 Ma. Transtension and transpression along the AFS are consistent with fault geometry.